Organizational Commitment as a Catalyst of the Influence of Transformational Leadership and Change Management on Performance - Fitriana, Herna Fita; Maliki, Budi Ilham; Komarudin, Mamay (Jurnal Economic Resource, 2025)
In the dynamic era of modern bureaucracy, improving employee performance is crucial. Public organizations, including the Regional People's Representative Council (DPRD) Secretariat in Banten Province, face the challenge of employee performance that remains below target. The main contributing factors include low work discipline, minimal training, and suboptimal leadership styles and change management. Transformational leadership and change management are believed to be able to increase organizational commitment, which has positive implications for employee performance. This study employed a quantitative approach with Partial Least Squares (PLS-SEM) analysis. The study population comprised all employees of the Regional People's Representative Council (DPRD) Secretariat in Banten Province, using the Hair et al. sampling technique, resulting in 195 respondents. The instrument was a questionnaire based on indicators of transformational leadership, change management, organizational commitment, and employee performance. Validity and reliability were tested using the outer and inner PLS models. The analysis showed that transformational leadership had a significant positive effect on organizational commitment and employee performance. Change management also significantly influenced both variables. Organizational commitment was shown to significantly mediate the relationship between the independent variables and employee performance. These findings prove that the combination of transformational leadership and effective change management can strengthen organizational commitment and drive optimal performance. This research contributes to the development of public sector HR management models and provides practical implications for strengthening adaptive and productive bureaucratic governance.